The prevalence of infectious bursal disease in chickens in Ethiopia: A systematic review and meta-analysis - Tibebu, A.; Bahiru, A.; Yitbarek, T.; Teshome, Y.; Tamrat, H.; Ferede, Y.; Assefa, Ayalew; Mekonnen, S.A. (Elsevier, 2025)
Infectious bursal disease (IBD) is a contagious viral disease in young chickens that weakens immunity and causes significant economic losses. This review updates IBD prevalence in Ethiopian chickens from 2000 to 2023. The review follows PRISMA and uses a random-effects model with the DerSimonian-Laird estimator. Of 245 retrieved studies, 22 (31 reports) were included in the meta-analysis. The pooled IBD prevalence was 67% (95% CI 56–75%; I² = 98.8%). Prevalence ranged from 85% in Addis Ababa (95% CI 81–89%) to 56% in southern NNP (95% CI 29–80%). Pooled prevalence was higher in serological studies (71%; 95% CI 60–80%) than in molecular (54%; 95% CI 20–85%) or postmortem studies (31%; 95% CI 29–33%). Pooled prevalence was higher in exotic chickens (65%; 95% CI 50–77%) than in indigenous chickens (61%; 95% CI 46–74%) and higher in adults (70%; 95% CI 60–78%) than in younger birds (65%; 95% CI 51–76%). Female chickens had a higher pooled prevalence (68%; 95% CI 55–79%) than males (62%; 95% CI 48–74%). Both classical virulent (cvIBDV) and very virulent (vvIBDV) serotype I genotypes have been identified in Ethiopia. The review underscores the urgent need for ongoing surveillance and national interventions to reduce IBD prevalence, which threatens poultry production and reproductive performance.